Pengembangan Media TESBOM (Teka-Teki Silang Blanded Of Matter) Berbasis Digital Web Untuk Meningkatkan Hasil Belajar Siswa Muatan IPAS Pada Kelas V SD - Radhisya Adristi Kusuma; Khamdun Khamdun; Lovika Ardana Riswari (Universitas Hamzanwadi, 2024)
Abstract: This research carries out using digital web-based TESBOM (blended of matter crossword) media on human breathing material which aims to test the effectiveness of digital web-based TESBOM media in improving student learning outcomes for science content in class V of SD N 4 Kedungcino. The digital web-based TESBOM media developed is an educational game media that is integrated with digital web technology and also IPAS content material. The development method used in this research is the ADDIE R&D model development method. The instruments used were pretest questions and posttest questions given to class V students at SD N 4 Kedungcino. The results of the media expert validity test are in the very appropriate category with an average of 93.25%. The results of the material expert validity test are in the very appropriate category with an average of 87.5%. The normality test of the pretest results obtained a significance (sig) of 0.143 > 0.05, while the posttest results obtained a significance (sig) of 0.106 > 0.05 so it can be said that the data distribution was normally distributed. The results of the N-Gain test obtained an increase in the average score of 0.5932 in the moderate category and in the quite decent category. Based on the results of the average score on the N-Gain test in this research, it can be concluded that the development of digital web-based TESBOM media can be used as a learning medium to improve student learning outcomes. Keywords: TESBOM, Digital Web, Learning Outcomes, IPAS.